Criminological Features of the Cybersecurity Threats (Law, State and Telecommunications Review, 2023)
[Purpose] Currently, novel tools have converted many traditional phenomena into cyber ones. The absence of a standardized terminology and classification of cybersecurity threats has raised significant concerns among researchers and lawmakers. Ignoring the emerging risks that necessitate appropriate responses is impracticable. Prior to devising countermeasures to combat cybercrime, it is imperative to accurately define the concept of cybersecurity threat and differentiate it from other related notions such as information security, computer security, cyberattack, cyberspace attack, cyber incident, cybersecurity incident, cyber threat, and cybersecurity event, whose definitions may be ascertained from the glossaries of various standardization institutes.[Methodology/Approach/Design] This study presents a descriptive investigation of cybersecurity threats and their causes, utilizing genetic, systematic-functional, and systematization methods. Cyberattacks are identified as the primary threat, and data is represented through qualitative research and summarized in tables. The study also considers the historical background of concepts and cyber-criminality.[Findings] The present study delves into a comprehensive analysis of distinct categories of cybersecurity threats, the trajectory of cybercrime, and the factors that underpin the emergence of new cybersecurity threats. The research scrutinizes both the general causes for cyber-criminality and the specific determinants for criminal activities that target the energy sector, a critical component of a state's infrastructure. The study reveals that the major sources of threats comprise terrorists, insiders (i.e., disgruntled employees), commercial spies, and black hackers or crackers, whose malicious acts are themselves considered threats to cybersecurity.